Separation of Cesium and Rubidium from Solution with High Concentrations of Potassium and Sodium - Junjie Xie; Kang Li; Zhuonan Shi; Changli Min; Shina Li; Zichen Yin; Ruixin Ma (Separations, 2023)
Solvent extraction with 4-tert-butyl-2-(α-methylbenzyl) phenol (t-BAMBP) is an effective method for the separation and purification of rubidium and cesium. A solution containing a high K+ concentration (exceeding 80 g/L), which was ultra-salty, with about 200 g/L alkali metal ions, was used to extract Rb+ and Cs+. The effects of the process parameters on the separation of cesium and rubidium were systematically studied. The optimum conditions were as follows: NaOH concentration of 0.5 mol/L, t-BAMBP concentration of 1 mol/L (in sulfonated kerosene), organic/aqueous volume ratio (O/A ratio) of 3:1, and contact time of 1 min. The extraction rates of cesium and rubidium were 99.81 and 98.09%, respectively, and 19.31% of potassium was co-extracted in the organic phase after five-stage countercurrent extraction. About 99.32% of K+ in the organic phase could be removed after five-stage countercurrent scrubbing with deionized water at an O/A ratio of 2:1 for 2 min. When 0.5 mol/L hydrochloric acid solution was used as detergent, almost all of the cesium and rubidium (>99%) could be recovered by two-stage countercurrent stripping at an O/A ratio of 3:1 for 2 min. A solid compound was found and collected from the organic phase during multi-stage solvent extraction. Its composition and structure were determined by XRD, infrared Fourier-transform, and ICP-MS.